2014
DOI: 10.1016/j.jnucmat.2014.07.032
|View full text |Cite
|
Sign up to set email alerts
|

3He bubble evolution in ErT2: A survey of experimental results

Abstract: a b s t r a c tFor the past several years we have been carrying out a long term experimental study of 3 He in ErT 2 (erbium di-tritide). This study has attempted to answer questions regarding the evolution of helium bubbles in ErT 2Àx He x . ErT 2 samples have been studied periodically over four years using Transmission Electron Microscopy (TEM), X-ray Diffraction (XRD), and Nano-Indentation (NI). In ErT 2Àx He x , helium bubbles are plate-like and grow along {1 1 1} planes. The bubbles grow in three distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Helium is insoluble in most materials and precipitates out of the matrix to form clusters and bubbles when the helium concentration is sufficiently high [ 2 , 3 , 4 ]. Helium agglomerates usually assume an over-pressurized spherical morphology in metal systems but can link to form platelets or other morphologies in some cases [ 5 , 6 , 7 , 8 ]. The addition of He often causes mechanical property degradation in materials [ 2 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Helium is insoluble in most materials and precipitates out of the matrix to form clusters and bubbles when the helium concentration is sufficiently high [ 2 , 3 , 4 ]. Helium agglomerates usually assume an over-pressurized spherical morphology in metal systems but can link to form platelets or other morphologies in some cases [ 5 , 6 , 7 , 8 ]. The addition of He often causes mechanical property degradation in materials [ 2 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the design of new substrates for high quality Ti film growth is in demand. Single crystal Si is a candidate substrate material due to its properties of high thermal and electrical conductivity [5,11,41]. However, the chemical reaction between Ti and Si to form a Ti-Si complex at high substrate temperature restricts its application [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Erbium is a vital candidate material for tritium storage in solid phase [1], due to its higher thermal stability of its tritide and better accommodation ability for helium atoms generated by the decay of tritium [2]. The He bubble evolution-induced mechanical property degradation impedes its application in the field of nuclear industry.…”
Section: Introductionmentioning
confidence: 99%
“…The nucleation, growing, and interacting of helium bubbles in the metal matrix attract much attention from investigators [8,9]. Snow et al [2] systematically studied the mechanism of 3 He bubble growth by transmission electron microscopy (TEM) with the aging of Er tritide up to the 3 He content of 0.37. It was found that the He bubbles grow as Griffith cracks [10] until the 3 He content of ~0.15, while the bubbles grow in thickness by punching dislocation dipoles with further aging [2,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation